(untitled) (ENTHYMEMA, 2025)
This article examines the stylistic characteristics of short aphoristic writings, taking into account the acquisitions of cognitive poetics. We reflect on the reasons why short communication has now taken full autonomy, especially in social media, compared to elaborate, literary or even essayistic or journalistic communication. Some examples of analysis are then provided, both in poetry (Valentino Zeichen) and in prose (Carla Vasio).